Histological and Biochemical Characterization of Polyembryony in Muvandan and Vellaikoluban Mangoes - Dhinesh Babu K (Department of Pomology & Floriculture,College of Horticulture, 2005)
The term 'polyembryony' (PE) encompasses a set of processes whereby adventive embryos are formed along with zygotic embryo resulting in the emergence of multiple seedlings from a single seed. Understanding the histological and histochemical changes underlying the PE, a developmentally fascinating phenomenon, generally observed in a number of mango cultivars of south west coast of India is critical for the successful utilization of the same in crop improvement and other aspects. The project on "Histological and biochemical characterization of polyembryony in Muvandan and Vellaikolumban mangoes" - two homestead mango cultivars of Kerala - was hence taken up at the Department of Pomology and Floriculture, College of Horticulture, Kerala Agricultural University during 2002-2004 for tracing and characterizing the various histological and biochemical changes taking place during embryogenesis in polyembryonic Muvandan and Vellaikolumban mangoes vis-a-vis monoembryonic Bangalora; for characterizing the polyembryony involving isozymes as genetic markers and for studying the effect of different seed treatments on the expression of polyembryony at the field level and the 'subsequent seedling growth and vigour. Histological investigations revealed that the sequence of events in zygotic embryo formation was similar in both polyembryonic and monoembryonic cultivars. Fertilization was observed within five days after anthesis in polyembryonic and monoembryonic cultivars. Endosperm formation began by 15 days after fertilization (DAF) when the embryos were at near heart shaped stage In Muvandan and Vellaikolumban. Radicle and plumule initials were visible by 20 DAF when the endosperrn development was near complete in Muvandan. Adventive embryonic initial cells (AEICs) appeared in the nucellus by 10 DAF and 15 DAF in Vellaikolumban and Muvandan, respectively, when the zygotic embryo was at near heart shaped stage and this could be the turning point as far as adventive embryogenesis is concerned. Nucellar embryogenesis was found to be invariably preceded by and closely dependent on zygotic embryogenesis. Such nucellar embryos